Leadless Left Bundle Branch Area Pacing in Cardiac Resynchronisation Therapy: Advances, Challenges and Future Directions - Wijesuriya, Nadeev; Elliott, Mark K.; Mehta, Vishal; Sidhu, Baldeep S.; Strocchi, Marina; Behar, Jonathan M.; Niederer, Steven; Rinaldi, Christopher A. (Frontiers in Physiology, 2022)
Leadless left bundle branch area pacing (LBBAP) represents the merger of two rapidly progressing areas in the field of cardiac resynchronisation therapy (CRT). It combines the attractive concepts of pacing the native conduction system to allow more physiological activation of the myocardium than conventional biventricular pacing, with the potential added benefits of avoiding long-term complications associated with transvenous leads via leadless left ventricular endocardial pacing. This perspective article will first review the evidence for the efficacy of leadless pacing in CRT. We then summarise the procedural steps and pilot data for leadless LBBAP, followed by a discussion of the safety and efficacy of this novel technique. Finally, we will examine how further mechanistic evidence may shed light to which patients may benefit most from leadless LBBAP, and how improvements in current experience and technology could promote widespread uptake and expand current clinical indications.